Testing of Resistivity of Dense Ash Slurry and Return Water from “Kostolac A” Power Plant under Laboratory Conditions - Kostic, Vojin Ivo (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
The paper presents the measurement results of the resistivity of dense ash slurry and return water mixture originated from the “Kostolac A” power plant. The four different ash slurry water mixtures with different ash concentrations are examined under laboratory conditions. The results of the carried tests are listed in the paper, and they strongly approve the practical implementation of the proposed measuring method.